2020
DOI: 10.3390/beverages6010016
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Macroelements, Transition Elements, and Anionic Contents of Commercial Roasted Ground Coffee Available in Jordanian Markets

Abstract: Coffee is one of the most common drinks worldwide. Due to the variability of elements composition, coffee is important for human health. The aim of this study is to assess the concentration of certain selected elements of commercial samples of roasted ground coffee available in Jordanian markets. The concentrations of macroelement components (sodium, potassium, and calcium), transition elements (lead, cadmium, iron, nickel, and copper), and anion contents (sulfate, nitrate, fluoride, chloride, and phosphate io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…As these belong to the macro elements, high amounts are to be expected. Several studies reported potassium, magnesium, and calcium as the highest concentrated elements in roasted coffee beans [56][57][58][59]. Ballesteros et al reported potassium as the most abundant element in a mixture of arabica and canephora CS, followed by magnesium [12].…”
Section: Ash Contents and Mineral Compositionmentioning
confidence: 99%
“…As these belong to the macro elements, high amounts are to be expected. Several studies reported potassium, magnesium, and calcium as the highest concentrated elements in roasted coffee beans [56][57][58][59]. Ballesteros et al reported potassium as the most abundant element in a mixture of arabica and canephora CS, followed by magnesium [12].…”
Section: Ash Contents and Mineral Compositionmentioning
confidence: 99%
“…Coffee is the most worldwide accepted beverage, which has become the second most valuable commodity after oil (Bae et al., 2014). It is the paramount commercialized product with over 3 billion cups of coffee drinks consumed worldwide every day (International Coffee Organization, 2020; Al‐Dalain et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Both metallic and non-metallic components are necessary for the human body's healthy growth, development, and optimal operation. It is therefore crucial to determine the presence of these elements in beverages, water, food, plants, and soil [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%